2014
DOI: 10.2139/ssrn.2486501
|View full text |Cite
|
Sign up to set email alerts
|

The Drivers of Long-Run CO2 Emissions: A Global Perspective Since 1800

Abstract: Fossil-fuel-related carbon dioxide emissions have risen dramatically since 1800. We identify the long-run drivers of CO 2 emissions for a sample of twelve developed economies using an extended Kaya decomposition. By considering biomass and carbonfree energy sources along with fossil fuels we are able to shed light on the effects of past and present energy transitions on CO 2 emissions. We find that at low levels of income per capita, fuel switching from biomass to fossil fuels is the main contributing factor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…(2016), Morales‐Lage et al . (2016) and Henriques and Borowiecki (2014) studies also confirmed the existence a long‐run positive relationship between energy, economic growth and CO2 emission. The last group of studies used panel smooth threshold regression such as Heidari et al .…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…(2016), Morales‐Lage et al . (2016) and Henriques and Borowiecki (2014) studies also confirmed the existence a long‐run positive relationship between energy, economic growth and CO2 emission. The last group of studies used panel smooth threshold regression such as Heidari et al .…”
Section: Introductionmentioning
confidence: 74%
“…The second group of studies focused on panel data analysis. Among others, Leitao (2014), Ab-Rahim and Xin-Di (2016), Balogh and Jámbor (2017), Livingston et al (2013), Zheng et al (2016), Morales-Lage et al (2016) and Henriques and Borowiecki (2014) studies also confirmed the existence a long-run positive relationship between energy, economic growth and CO2 emission. The last group of studies used panel smooth threshold regression such as Heidari et al (2015), Mohammadi (2016), Aye and Edoja (2017) and Mahmut and Sinan (2016).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…As reported in the previous section, possible explanations can be related to changes in technologies, to variations in the energy mix or to variations in the contribution provided by the different economic sectors to the GDP generation[24,25,[35][36][37][38][39][40]. majority of the other European Countries[26]. China (-37.9%) and Easter European countries as Estonia (-48.7%), Poland (-42.9%), Slovak Republic (-42.6%) had the largest reduction of energy intensity.…”
mentioning
confidence: 99%
“…O conceito de IPAT, quando aplicado para emissões de GEE (Lima et al, 2016) é, por vezes, conhecida como Identidade de Kaya (Kaya, 1989). Este relação foi utilizada por Kaya que desenvolveu uma decomposição matemática cujo objetivo foi quantificar as emissões de dióxido de carbono, frente ao consumo energético e a intensidade carbônica (Henriques & Borowiecki, 2014). Com esse recurso, tenta-se convergir para um cenário de adoção de novas tecnologias que possuam menor potencial poluidor (Alvim & Santin, 2008b…”
Section: Ipat E Identidade De Kayaunclassified